Does Gender Matter? An Exploratory Study of Cultural Betrayal Trauma and Hallucinations in Latino Undergraduates at a Predominantly White University - Gómez, Jennifer M. (Journal of interpersonal violence, 2021)
Violence victimization, such as physical, sexual, and emotional abuse, has been linked with hallucinations. How abuse-related distress manifests is dependent on a host of factors, including gender, ethnicity, and societal inequality. Cultural betrayal trauma theory may provide insight into hallucinatory experiences for Latinos in the United States, as it is a contextualized framework that identifies societal trauma (e.g., discrimination) as a contributor to the harm of within-group interpersonal violence victimization in minority populations. Though men may experience higher rates of hallucinations, there is little work on gender differences in the predictive power of violence victimization on hallucinations, particularly in Latino populations. Therefore, with cultural betrayal trauma theory as a guide, the purpose of the current exploratory study is to examine gender differences in the association of ethno-cultural betrayal trauma (within-group violence victimization) on tactile, visual, and auditory hallucinations in a sample of Latino undergraduate students at a predominantly White university in the United States. Participants (N = 80) completed online self-report measures on ethno-cultural betrayal trauma and hallucinatory experiences. Sizable proportions of the sample reported experiencing ethno-cultural betrayal trauma and tactile, visual, and auditory hallucinations. Controlling for between-group trauma, the link between ethno-cultural betrayal trauma and tactile, visual, and auditory hallucinations was moderated by male gender. With cultural betrayal trauma theory as its framework, these preliminary results suggest that gender differences in hallucinatory experiences may be affected by the way trauma-related distress is expressed in Latino undergraduate students in the United States.